Women's writing in Italy, 1400-1650 - Cox, Virginia (Johns Hopkins University Press, 2008)
This is the first comprehensive study of the remarkably rich tradition of women's writing that flourished in Italy between the fifteenth and early seventeenth centuries. Virginia Cox documents this tradition and both explains its character and scope and offers a new hypothesis on the reasons for its emergence and decline.